PENGELOLAAN ZAKAT PROFESI (Studi Kasus di Kantor Kementerian Agama Kabupaten Magetan) - Taufiqurrahman, Ahmad (LIPI, 2019)
Zakat is a valuable asset for Muslims because it functions as a potential source of funds that can be utilized to improve the welfare of the whole community, especially in the areas of poverty alleviation, ignorance and underdevelopment. Management of zakat by an institution, especially those that have formal legal force, will have several advantages, including: First, to ensure the certainty and discipline of zakat payers. Second, to maintain the inferiority feeling of the mustahiks of zakat when dealing directly to receive alms from the muzakki. Third, to achieve efficient and effective, as well as the right target in the use of zakat assets according to the priority scale that exists in a place. Fourth, to show the symbols of Islam.